Preliminary Investigation on Spiders (Arachnida: Araneae) in Rani Veerangana Durgawati Wildlife Sanctuary, Damoh, Madhya Pradesh, India - Patil, Sachin R.; Sambath, S.; Bhandari, Rita (Indian Forester, 2013)
A preliminary study of spider fauna of the RVDWLS was carried out during 2009-2011. The present findings indicated that a total 23 spider species belonging to 12 genera under 7 families were reported for the first time from the sanctuary. Lycosidae was the most diverse family followed by Araneidae, Nephilidae, Oxyopidae, Clubionidae, Ctenidae and Salticidae. The abundance of the Lycosid spiders is mainly attributed to adequacy of leaf- litter in tropical mixed dry deciduous forest. Based on categorization of spiders into habit-wise functional groups, the ground hunters were dominating the foliage orb weavers and foliage hunters. The study has also indicated that there are new records of family, genus and species to the spider fauna of Madhya Pradesh.